2012
DOI: 10.1155/2012/540273
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Oestrogen and Other Hormones in the Pathophysiology and Treatment of Schizophrenia

Abstract: The theory that many serious mental illnesses, in particular psychoses such as schizophrenia, may have a significant hormonal aetiological component is fast gaining popularity and the support of scientific evidence. Oestrogen in particular has been substantially investigated as a potential mediator of brain function in schizophrenia. Epidemiological and life-cycle data point to significant differences in the incidence and course of schizophrenia between men and women suggests a protective role of oestrogen. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 83 publications
4
31
0
1
Order By: Relevance
“…Many studies have also confirmed estrogen's influence on the central neurotransmitter systems, thus indicating that it may have an antipsychotic activity (for a review see Hayes et al 2012). This corresponds to the lower PANSS scores in females than in males that were observed in our study group.…”
Section: Discussionsupporting
confidence: 79%
“…Many studies have also confirmed estrogen's influence on the central neurotransmitter systems, thus indicating that it may have an antipsychotic activity (for a review see Hayes et al 2012). This corresponds to the lower PANSS scores in females than in males that were observed in our study group.…”
Section: Discussionsupporting
confidence: 79%
“…For example, one study showed that estrogen depletion via ovariectomy in rats increased DA D 2 receptor densities in the nucleus accumbens and caudate nucleus, and estrogen treatment reversed the increase and further reduced DA D 2 receptor levels (Chavez et al, 2010). This is consistent with evidence that the behavioral response to antipsychotic drugs, which are DA D 2 antagonists, are decreased following ovariectomy in female rats (Arad and Weiner, 2012) and that estrogen treatment ameliorates psychotic symptoms in humans (Hayes et al, 2012). …”
Section: Hormones and Psychosissupporting
confidence: 89%
“…Recent comprehensive reviews of the research findings (Hayes et al, 2012; Markham, 2011) concluded the following about estrogen: 1) women with schizophrenia manifest reduced estrogen levels compared to healthy same-sex controls, 2) peak bone mass, an indicator of cumulative estrogen exposure, is significantly lower in women with first episode schizophrenia than in matched controls, 3) in adulthood, risk for psychosis is higher during periods of low estrogen (e g., during the low estrogen follicular phase of the menstrual cycle and postmenopausal), and 4) adjunctive estradiol may reduce symptom severity in psychotic women. Although the mechanisms involved in the relation of estrogen with psychotic disorders are not understood, it has been suggested that they may reflect anti-dopaminergic and/or neuroprotective effects (Arad and Weiner, 2009).…”
Section: Hormones and Psychosismentioning
confidence: 99%
“…Indeed, these differences have also been observed in various animal models of aspects of schizophrenia (Hill, 2015). The underlying neurobiological basis for these differences has been linked to sex hormones, in particular oestrogen which is thought to be protective (Hayes et al, 2012). Thus, consistent with recent NIH guidelines, there is a need to also incorporate females in future studies (Clayton and Collins, 2014;Crawford and DeLisi, 2016).…”
Section: Speciesmentioning
confidence: 93%